Addressing Brain Drain: Retaining Skilled Professionals in Nepal in Manufacturing Sector from the Perspective of Human Resource Management - Baral, Anil Kumar (Journal of Advanced Academic Research, 2023)
Retaining skilled professionals in Nepal's manufacturing sector is crucial for organizational success and sustainable economic development. However, the phenomenon of brain drain poses significant challenges in this regard. This article, from the perspective of human resource management (HRM), explores the factors contributing to brain drain in Nepal and offers insights on addressing this issue. From an HRM perspective, this article examines the reasons behind employee dissatisfaction and the challenges faced by manufacturers in retaining skilled professionals. To improve employee retention, this article highlights key areas for consideration. It emphasizes the importance of workplace happiness, factors such as the weight of job responsibilities and safe working conditions, and the critical role of competitive salaries in satisfying employee needs. Furthermore, it introduces six elements - inclusion, appreciation, support, trust, purpose, and achievement - that, when incorporated into organizations, can contribute to positive workplace well-being and employee satisfaction.In conclusion, this article calls for collective efforts in fostering an environment of trust, communication, and inclusivity within manufacturing organizations. Recognizing and appreciating employee contributions, providing clear responsibilities and focusing on employee satisfaction are vital for retaining skilled professionals and addressing the challenges posed by brain drain in Nepal's manufacturing sector.